The Use of Chatgpt by EFL Teachers: Utilization and Challenges Perceived - Pramudia, Muhammad Miikaa-iil Putra; Madjid, Hilda Izzati; Feriyal (ICONELT, 2024)
The development of artificial intelligence (AI) has created changes in various educational practices, including the field of English language teaching for EFL learners. This research explores the utilization of the most recognized AI tool, Chat GPT, conducted by teachers in the context of EFL practices. This research aims to identify the benefits, challenges, and future planning related to the Chat GPT utilization recognized by local teachers from local State madrasa in Surabaya through a qualitative interview. The result indicated that most of the teachers showed a positive attitude towards the AI abilities in giving feedback, generating diverse educational material, and facilitating more productivity, but also raised concern related to the academic dishonesty, risk of being over-reliant, and lack of supervision during its practice. Highlighting the need for future planning required to address these issues that involves various stakeholders’ cooperation.